Mechanism for meeting the care of older adults in rural China—relying on spouse, offspring or community? - Ziyue Dong; Jianliang Nie; Dan Li; Yufeng Wu (BMC Geriatrics)
Abstract Background Within the population aging and the trend of aging in place on the rise, it is crucial to explore how care needs are being met for this demographic within the community. Methods This study utilizes data from the 2019–2021 survey on 1,126 rural older adults aged 60 years and above across 11 provinces and 31 villages in China. This study aims to examine the influence of spouse, offspring, and community status on the extent to which the care needs of rural older adults are met. Furthermore, it seeks to clarify the underlying mechanism of influence, as well as the change that occurs throughout the life cycle, using a multiple linear regression analysis. Results This study demonstrates that the health status of spouses, the education level of offspring, the relationship with offspring, and the living with offspring significantly and positively influence the meeting of care needs among rural older adults. Notably, older adults with healthier spouses experience a 14.5% greater fulfillment of care needs compared to those without partners. Furthermore, those living with their offspring experience a 10.6% higher degree of care met. Additionally, the construction and operation of community senior care facilities, indicative of community quality, significantly enhance the meeting of care needs among rural older adults, with a 16.0% increase in met needs for those residing in communities equipped with such facilities compared to those without. From a life cycle perspective, the aforementioned significant effects are only observed among rural older adults aged 60–74 years or those in better health. Conclusion Our results indicate the meeting of the care needs among rural older adults is influenced by the quality of their spouse, offspring, and community, with these effects diminishing later in the life cycle.